Certified randomness using a trapped-ion quantum processor - Minzhao Liu; Ruslan Shaydulin; Pradeep Niroula; Matthew DeCross; Shih-Han Hung; Wen Yu Kon; Enrique Cervero-Martín; Kaushik Chakraborty; Omar Amer; Scott Aaronson; Atithi Acharya; Yuri Alexeev; et al. (Nature, 2025)
Abstract Although quantum computers can perform a wide range of practically important tasks beyond the abilities of classical computers1,2, realizing this potential remains a challenge. An example is to use an untrusted remote device to generate random bits that can be certified to contain a certain amount of entropy3. Certified randomness has many applications but is impossible to achieve solely by classical computation. Here we demonstrate the generation of certifiably random bits using the 56-qubit Quantinuum H2-1 trapped-ion quantum computer accessed over the Internet. Our protocol leverages the classical hardness of recent random circuit sampling demonstrations4,5: a client generates quantum ‘challenge’ circuits using a small randomness seed, sends them to an untrusted quantum server to execute and verifies the results of the server. We analyse the security of our protocol against a restricted class of realistic near-term adversaries. Using classical verification with measured combined sustained performance of 1.1 × 1018 floating-point operations per second across multiple supercomputers, we certify 71,313 bits of entropy under this restricted adversary and additional assumptions. Our results demonstrate a step towards the practical applicability of present-day quantum computers.